Expert goalkeepers` and coaches` views on anticipation and cue utilisation facing backcourt throws in handball goalkeeping - Huesmann, K.; Schorer, J.; Büsch, D.; Witt, J.; Loffing, F. (Frontiers in Sports and Active Living, 2023)
Introduction: Handball goalkeepers have to act under severe spatio-temporal pressure in both standardised (e.g., 7 m penalty) and non-standardised situations (e.g., backcourt throws) which require them to predict action outcome before ball flight is visible. So far, research on goalkeepers` cue utilisation for anticipation of an opponent`s action has mainly focused on 7 m throw situations whereas little attention has been paid to the latter, more complex and far more frequently occurring backcourt throw situations.